The predictive role of impulsivity and perceived social support in psychiatric symptoms of women with methamphetamine use disorder - Wang, Shuzhe; Li, Jing; Li, Yibo; Xia, Yuwei; Gong, Yu; Mao, Fuqiang (Frontiers in Psychiatry, 2023)
Abstract Background: Currently, few studies have examined the mental states of Women methamphetamine patients, and the influence of impulsivity and perceived social support on substance misuse-induced mental disorders is unclear. We want to examine the mental state of women with methamphetamine use disorder and compare it to the Chinese norm value of healthy women. Investigate the connection between impulsivity, perceived social support and mental state of women with methamphetamine use disorder . Method: 230 women subjects with a history of methamphetamine usage were recruited. The Chinese version of the SCL-90-R(SCL-90) was used to evaluate psychological health problems, while the Multidimensional Scale of Perceived Social Support(MSPSS) and Barratt Impulsiveness Seale-11(BIS-11) were utilized to evaluate perceived social support and impulsivity, respectively. The t-test, Pearson correlation analysis, multivariable linear regression, stepwise regression models, moderating effect analysis were used to analyze the statistics. Results: There was a noticeable difference between the Chinese norm and all participants' SCL-90 ratings, especially for Somatization (t = 24.34, p < 0.001), Anxiety (t = 22.23, p < 0.001), Phobic anxiety (t = 26.47, p < 0.001), and Psychoticism (t = 24.27, p < 0.001). In addition, perceived social support levels and impulsivity levels are independently predictive of SCL-90 scores. Lastly, the impact of Impulsivity on SCL-90 can be modulated by perceived social support. Conclusion: According to this study, women with methamphetamine use disorder have worse mental health conditions compared to healthy subjects. Furthermore, certain psychological symptoms associated with methamphetamine use in women can be aggravated by impulsivity, while perceived social support acts as a protective factor for methamphetamine-related psychiatric symptoms. Specifically, perceived social support weakens the impact of impulsivity on psychiatric symptoms in women with methamphetamine use disorder.